Agmatine Mitigates Acetaminophen-induced Acute Liver Injury in Mice: Involvement of HMGB1/RAGE/NFκB and Nrf2/HO-1 Signaling Pathways - Ahmed Abdelhady; Mohammed Ayman; Marwa Abdelmageed (Journal of Applied Veterinary Sciences, 2025)
An overdose of acetaminophen (APAP) is considered one of the primary sources of drug-induced liver injury. This study aimed to explore the mechanism of agmatine (Agma) against APAP-induced acute liver injury (ALI) in mice. Mice were allocated into six groups: normal and Agma control, APAP, N-acetyl-L-cysteine (NAC) + APAP, Agma 100 mg/kg + APAP, and Agma 200 mg/kg + APAP. After 24 h from APAP injection, tissues and serum were gathered. Compared with APAP group, Agma pretreatment ameliorated liver injury, increased hepatic reduced glutathione (GSH), decreased serum biomarkers and decreased hepatic malondialdehyde (MDA) content. Additionally, Agma administration reduced hepatic levels of high-mobility group box 1 (HMGB1), receptor for advanced glycation end products (RAGE), Toll-like receptor 4 (TLR4), nuclear factor kappa B-p 65 subunit (NFκB-p65), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). Moreover, Agma administration decreased hepatic kelch-like ECH-associated protein 1 (Keap1) and up-regulated hepatic nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) levels. Noteworthy, the Agma 200 mg/kg effect on the reduction of hepatic inflammatory and oxidative stress biomarkers was more pronounced as compared to Agma 100 mg/kg prior APAP challenge. The study demonstrated that Agma can reduce inflammation and oxidative damage induced by APAP, and the mechanism may be related to the signal transduction factors on the HMGB1/RAGE/NFκB pathway and the Nrf2/HO-1 signaling pathway.